Emotional Intelligence, Job Satisfaction, Emotional Exhaustion, and Subjective Well-Being in High School Athletic Directors. Issue 6 (December 2020) - Lee, Ye Hoon; R. Richards, K. Andrew; Washhburn, Nicholas S.
Developing subjective well-being among educational leaders is beneficial for both leaders themselves and students. Evidence has suggested that emotional intelligence has implications for the mental and physical well-being of individuals in leadership positions. This relationship has not, however, been extensively investigated among school administrators, particularly athletic directors, who can influence the lives of student-athletes. Thus, this study sought to examine the relationships among emotional intelligence, job satisfaction, emotional exhaustion, and subjective well-being in high school athletic directors. Participants included 394 U.S. high school athletic directors who completed questionnaires relating to emotional intelligence, job satisfaction, emotional exhaustion, and subjective well-being. The results revealed positive associations between emotional intelligence and subjective well-being and also demonstrated that both job satisfaction and emotional exhaustion mediated the emotional intelligence-subjective well-being relationship. The results highlight the role of emotional intelligence in athletic directors' subjective well-being and suggest that athletic directors should take measures to increase their emotional intelligence through professional learning opportunities and school support structures.